Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide

Observation of photoconductivity in Sn-doped ZnO nanowires and their photoenhanced field emission behavior - Sheini, Farid Jamali; More, Mahendra A.; Jadkar, Sandesh R.; Patil, K. R.; Pillai, Vijaymohanan K.; Joag, Dilip S. (Journal of Physical Chemistry C, 2010)
Sn-doped ZnO nanowire films have been Successfully synthesized by electrodeposition oil zinc foil followed by annealing in air at 400 degrees C for 4 h. The XRD patterns of the annealed specimens exhibit I set of well-defined diffraction peaks indexed to the wurtzite phase of ZnO. The Surface morphology of the as-synthesized films showed a network of densely packed flakes/sheets oil the Substrate. However, upon annealing, the formation of ZnO nanowires, processing length in the range of several micrometers and diameter less than 150 nm, oil the entire substrate is observed. The relative atomic percentage of Sri, estimated from the energy dispersive spectra, was found to be 0.5 and 2.0 in the ZnO films deposited for 10 and 40 min durations, respectively. Front the field emission studies, the Values of the turn-on field and threshold field, required to draw emission Current density of 10 and 100 mu A/cm(2), are observed to be 0.68 and 1.1 V/mu m for 0.5% Sn-doped ZnO and 1.72 and 2.25 V/mu m for 2.0% Sn-doped ZnO, respectively. The field emission Current stability investigated for a duration Of h at the preset value of 100 mu A is found to be excellent. A prominent photoenhancement in the field emission Current upon visible light illumination of the Sn-doped ZnO nanowires films has been observed. This enhancement has been attributed to the photoconductivity of the Sn-doped ZnO.